Applied Graph Data Science: Graph Algorithms and Platforms, Knowledge Graphs, Neural Networks, and Applied Use Cases - Raj, Pethuru; Dutta, Pushan Kumar; Chong, Peter Han Joo; Song, Houbing Herbert; Zaitsev, Dmitry A (Elsevier Science & Technology, 2025)
Applied Graph Data Science: Graph Algorithms and Platforms, Knowledge Graphs, Neural Networks, and Applied Use Cases delineates how graph data science significantly empowers the application of data science.The book discusses the emerging paradigm of graph data science in detail along with its practical research and real-world applications.